Maternal transient receptor potential vanilloid 6 (Trpv6) is involved in offspring bone development - Fecher-Trost, Claudia; Lux, Femke; Busch, Kai-Markus; Raza, Ahsan; Winter, Manuel; Hielscher, Franziska; Belkacemi, Thabet; Eerden, Bram van der; Boehm, Ulrich; Freichel, Marc; Weißgerber, Petra (Journal of bone and mineral research, 2019)
Embryonic growth and bone development depend on placental Ca2+ transport across the feto-maternal barrier to supply minerals to the fetus. The individual factors and cellular mechanisms that regulate placental Ca2+ transfer, however, are only beginning to emerge. We find that the Ca2+-selective transient receptor potential vanilloid 6 (TRPV6) channel is expressed in trophoblasts of the fetal labyrinth, in the yolk sac, and in the maternal part of the placenta. Lack of functional TRPV6 channels in the mother leads to a reduced Ca2+ content in both placenta and embryo. Ca2+ uptake in trophoblasts is impaired in the absence of Trpv6. Trpv6-deficient embryos are smaller, have a lower body weight, and shorter and less calcified femurs. The altered cortical bone microarchitecture persists in adulthood. We show that TRPV6's Ca2+-conducting property causes this embryonic and bone phenotype. Our results show that TRPV6 is necessary for the Ca2+ uptake in trophoblasts and that TRPV6 deficiency in the placenta leads to reduced embryo growth, minor bone calcification, and impaired bone development. © 2019 American Society for Bone and Mineral Research.
Gesehen am 16.04.2020